Susceptibility of 1,500 Isolates of Pseudomonas aeruginosa to Gentamicin, Carbenicillin, Colistin, and Polymyxin B - Duncan, Ian B. R. (1974)
A series of 1,500 strains of Pseudomonas aeruginosa was collected from a variety of sources to provide a group of strains which would truly represent the species. All of them were pyocine typed, and a wide range of types was included among the isolates from each source. The gentamicin, carbenicillin, colistin, and polymyxin minimal inhibitory concentration of each strain was measured by the agar dilution method employing the Steers inocula replicator. Over 99% of strains were inhibited by 8 μg of gentamicin per ml, by 256 μg of carbenicillin per ml, and by 4 μg of colistin per ml. The small number of strains more resistant to each antibiotic comprised a variety of different pyocine types. Few strains were found to be susceptible to tetracycline, chloramphenicol, kanamycin, or streptomycin at the single concentration tested.